Dentist profile in the oral health teams and participation in permanent education actions in - Emmi, Danielle Tupinamba; Lima, Zaryff Said de; Miranda, Mayara Sabrina Luz (Journal of Health Care, 2021)
should take place on a daily basis, based on the problems found in the institutions. Objective: To know the professional profile of dentists working in Oral Health Teams (OHT) in the North region of Brazil, and to analyze the PHE actions with participation of this professional. Methods: This was a descriptive documentary study, with data collected from the 2nd cycle of the Program for Improving Access and Quality of Primary Care (PMAQ-AB), module VI, of 2014, with 1,189 dentists working in the OHT in the North region of Brazil. Results: Most dentists did not have a graduate degree and had worked for up to 3 years in OHT (74.3%). Most entered the service by public tender (42.4%), although the "recommendation" (30.6%) is the predominant form in the states of Amapá (55.9%), Amazonas (35.6%) and Pará (38.9%). Predominantly they had temporary employment contract (48.1%), where the state of Amapá stood out for the presence of 83.1% dentists with this employment contract. The majority participated in PHE actions (69.6%), mainly the states of Amazonas (79.8%) and Tocantins (74.7%). Among the PHE actions with participation of the dentist, there were presential activities (85.2%) and exchanges of experiences (33.3%). Conclusion: The type of employment contract of the dentist can generate professional instability and little interaction with the health system. New strategies and information technologies are still poorly explored as methods for PHE in the Northern Region.